2017
DOI: 10.1021/acs.est.7b03875
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Enteric Viruses with Microbial Compounds: Implication for Virus Persistence and Disinfection Treatments

Abstract: Although the interaction between phages and bacteria has already been well described, it only recently emerged that human viruses also interact with bacteria in the mammalian gut. We studied whether this interaction could occur in tap water and thus confer enteric viruses protection against temperature and the classical disinfection treatments used in drinking water production. We demonstrated that the addition of lipopolysaccharide or peptidoglycan of bacterial origin to enterovirus provides thermal protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…Bacterial surface glycans can also benefit viruses through other direct interactions. These molecules can stabilize viral particles but also enhance binding to viral receptors (1214, 16). Our binding assays suggested that HAstV attachment to host cells is not altered by incubation at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial surface glycans can also benefit viruses through other direct interactions. These molecules can stabilize viral particles but also enhance binding to viral receptors (1214, 16). Our binding assays suggested that HAstV attachment to host cells is not altered by incubation at 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Heat inactivation is commonly used for studying virus survival in water. In low temperature range (<50°C), the inactivation of naked viruses mainly comes from the denaturation of capsids (Waldman et al, 2020(Waldman et al, , 2017. However little is known concerning enveloped viruses.…”
Section: Temperature-based Inactivation Unrevealed Different Status Fmentioning
confidence: 99%
“…Many studies have shown that the virus–solid particle interactions can interrupt the disinfection processes [109,110]. Free and particle-associated noroviruses have provided different results in disinfection studies [111,112].…”
Section: Further Studiesmentioning
confidence: 99%